1974
DOI: 10.1161/01.cir.50.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine (Neo-synephrine) Terminated Ventricular Tachycardia

Abstract: Five cases of recurrent, wide QRS complex tachycardia which could be terminated with phenylephrine are presented. These cases fulfilled all accepted criteria for ventricular tachycardia. Carotid sinus massage with and without edrophonium hydrochloride had no effect on the ventricular activity but selectively slowed the atrial rate in cases of atrioventricular (A-V) dissociation, or blocked retrograde conduction in cases of A-V association. The mechanism of action of phenylephrine remains unclear.These cases ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 24 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…More relevant to the current topic are the few clinical studies examining the effects of reflexly induced vagal hyperactivity, mostly on ventricular arrhythmias. Waxman and colleagues provided the first evidence that some ventricular tachycardias (VTs) could respond to vagal activation, contrary to traditional belief [27,28], and that ventricular automaticity was decreased by vagal activity [29].…”
Section: Vagal Stimulation and Arrhythmias In Patientsmentioning
confidence: 99%
“…More relevant to the current topic are the few clinical studies examining the effects of reflexly induced vagal hyperactivity, mostly on ventricular arrhythmias. Waxman and colleagues provided the first evidence that some ventricular tachycardias (VTs) could respond to vagal activation, contrary to traditional belief [27,28], and that ventricular automaticity was decreased by vagal activity [29].…”
Section: Vagal Stimulation and Arrhythmias In Patientsmentioning
confidence: 99%
“…In this view, micro-re-entry occurring in the right ventricle would be more plausible, but the effects of atrial pacing during tachycardia do not support this hypothesis. Anyhow, the role of vagal action in terminating the arrhythmia argues against a ventricular origin, though this proof is not definite (Waxman et al, 1974). Moreover, the latter explanation does not take into account the similarity between the preexcitation beats induced by atrial premature stimulation and those seen during tachycardia.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to sympathetic stimulation, VNS decreased the maximum slope of APD restitution, attenuated electrical alternans, and increased ventricular ERP and VF thresholds. 87 Waxman et al provided early clinical evidence, which demonstrated that VTs could respond to vagal activation, contrary to traditional belief, 88,89 and that ventricular automaticity was decreased by vagal activity. 90 Subsequently, experimental animal data in conscious dogs clearly demonstrated that increasing vagal tone by means of right vagus nerve stimulation can prevent ventricular tachyarrhythmias in a model with healed myocardial infarction, evaluated with exercise testing and intermittent ischaemia.…”
Section: Vagal Stimulation and Ventricular Electrophysiologymentioning
confidence: 97%